Growth, morphological and photosynthetic characteristics, antioxidant capacity, biomass yield and water use efficiency of Gynura bicolor DC exposed to super-elevated CO2. (September 2015) - Wang, Minjuan; Dong, Chen; Fu, Yuming; Liu, Hong
Abstract: As a consequence of the increasing importance of leaf vegetables in Bioregenerative life support system (BLSS), there is an interest in enhancing both the productivity and quality of Gynura bicolor DC ( G. bicolor ). The effects of super-elevated carbon dioxide concentration (3000 ppm) on G. bicolor in different periods were investigated to reveal plausible underlying mechanisms for the growth, photosynthetic characteristics, antioxidant capacity and biomass yield. Experimental results showed that not only the photosynthetic rate but also the antioxidant capacity were increased in short-term super-elevated CO2 concentration. However, under long-term super-elevated CO2 concentrations, photosynthetic rate and pigment contents of G. bicolor significantly decreased due to photo inhibition. Elevated CO2 can be able to dwarf the G. bicolor plants. The leaves in high CO2 concentration were curled, which may affect the photosynthetic efficiency. At 3000 ppm level, leaf senescence accelerated but biomass yield had no significant difference. Furthermore, elevated CO2 controlled transpiration rate and then enhanced water use efficiency. Superoxide dismutase (SOD) activity, peroxide activity (POD) and total antioxidant capacity (T-AOC) in 3000 ppm condition were significantly lower than that in 400 ppm condition. On the contrary, catalase (CAT) activity, glutathione (GSH) content and hydrogen peroxide (H2 O2 ) were significantly enhanced under high CO2 concentration. Highlights: A and antioxidant capacity increased in short-term super-elevated [CO2]. A and pigment contents significantly decreased in long-term super-elevated [CO2]. Elevated CO2 controlled transpiration rate and then enhanced water use efficiency. Elevated CO2 can be able to dwarf the G. bicolor plants.